Analisis Efektivitas Sistem Informasi Jkn Mobile Dalam Meningkatkan Kualitas Layanan BPJS Kesehatan Di Mamuju, Sulawesi Barat - Nirmayanti Basri; Muh AL Khausari R Manora Y; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
Digital transformation in healthcare services requires BPJS Kesehatan to develop technology-based service platforms, one of which is through the JKN Mobile application. This application is designed to make it easier for participants to access administrative services, membership information, availability of health facilities, online queues, and online consultations. However, the effectiveness of its implementation in non-metropolitan areas such as Mamuju, West Sulawesi, has rarely been analyzed comprehensively. This study aims to evaluate the effectiveness of JKN Mobile in improving the quality of BPJS Kesehatan services through a quantitative approach using the DeLone & McLean information system success model. This study analyzes the influence of system quality, information quality, and application service quality on user satisfaction and perceptions of the quality of BPJS Kesehatan services. Data were collected from 20-30 active JKN Mobile users in Mamuju Regency and analyzed using multiple linear regression. The results of the study show that these three quality variables have a significant effect on the effectiveness of digital services. In addition, this study found obstacles in the form of limited network access, uneven levels of digital literacy, and the readiness of health facilities to integrate online service processes. This study makes an important contribution to strengthening the literature on health information systems in developing regions and provides a basis for BPJS Kesehatan to improve the equitable distribution of digital services throughout Indonesia.